Clinical phenotypes of infantile onset CACNA1A-related disorder. (January 2021) - Gur-Hartman, Tamar; Berkowitz, Oren; Yosovich, Keren; Roubertie, Agathe; Zanni, Ginevra; Macaya, Alfons; Heimer, Gali; Dueñas, Belén Pérez; Sival, Deborah A.; Pode-Shakked, Ben; López-Laso, Eduardo; Humbertclaude, Véronique; et al.
Abstract: Background: CACNA1A- related disorders present with persistent progressive and non-progressive cerebellar ataxia and paroxysmal events: epileptic seizures and non-epileptic attacks. These phenotypes overlap and co-exist in the majority of patients. Objective: To describe phenotypes in infantile onset CACNA1A- related disorder and to explore intra-familial variations and genotype-phenotype correlations. Material and methods: This study was a multicenter international collaboration. A retrospective chart review of CACNA1A patients was performed. Clinical, radiological, and genetic data were collected and analyzed in 47 patients with infantile-onset disorder. Results: Paroxysmal non-epileptic events (PNEE) were observed in 68% of infants, with paroxysmal tonic upward gaze (PTU) noticed in 47% of infants. Congenital cerebellar ataxia (CCA) was diagnosed in 51% of patients including four patients with developmental delay and only one neurological sign. PNEEs were found in 63% of patients at follow-up, with episodic ataxia (EA) in 40% of the sample. Cerebellar ataxia was found in 58% of the patients at follow-up. Four patients had epilepsy in infancy and nine in childhood. Seven infants had febrile convulsions, three of which developed epilepsy later; all three patients had CCA. Cognitive difficulties were demonstrated in 70% of the children. Cerebellar atrophy was found in only one infant but was depicted in 64% of MRIs after age two. Conclusions: Nearly all of the infants had CCA, PNEE or both. Cognitive difficulties were frequent and appeared to be associated with CCA. Epilepsy was more frequent after age two. Febrile convulsions in association with CCA may indicate risk of epilepsy in later childhood. Brain MRI was normal in infancy. There were no genotype-phenotype correlations found. Highlights: Paroxysmal non-epileptic events are the most common presenting phenotype. Paroxysmal tonic upward gaze is the most common paroxysmal event in infancy. Episodic ataxia is the most common paroxysmal event in childhood. Cognitive difficulties are common and associated with congenital cerebellar ataxia. Epilepsy is not rare and febrile convulsions in association with CCA may indicate risk of epilepsy in later childhood.